Technological improvements on classroom community and the increasing acceptance of distance learning courses. (1st January 2012) - Changchit, Chuleeporn; Klaus, Tim
Educators and students across the country are embracing the idea of increased distance learning and online course offerings from universities. The increased acceptance of online classes is supported by several key factors. Most notable of these factors include an increase of basic computer knowledge, faster means of communication between computers and more widespread access to computers. In addition to those factors, there are many social aspects that lend themselves to the acceptance of distance learning opportunities that include an increase in enrolment over the past several years due to more limited opportunities in the job market and a change in family dynamics. This study examines community factors which impact the classroom environment by comparing perceptions of students taking the same class from the same instructor in online and traditional classroom settings. The results reveal that these community factors were perceived differently by students in the two groups which lead to different level of satisfaction. The results in this study help in identifying key differences in student perceptions of the course and promote an understanding on whether there is a positive or negative perception in student satisfaction related to these community factors.